2011
DOI: 10.5146/tjpath.2011.01064
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of transbronchial needle aspiration cytology in sarcoidosis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Two studies [25,26] did not find any significant statistical difference. Six studies analyzed lymph node station as the predictor in patients with suspected sarcoidosis [27,28,29,30,31,32], but each one reported different results and the only investigation reporting statistical analysis showed no difference among the stations sampled [30]. One study was performed in patients with suspected tuberculosis and reported the highest accuracy for station 7 [33].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [25,26] did not find any significant statistical difference. Six studies analyzed lymph node station as the predictor in patients with suspected sarcoidosis [27,28,29,30,31,32], but each one reported different results and the only investigation reporting statistical analysis showed no difference among the stations sampled [30]. One study was performed in patients with suspected tuberculosis and reported the highest accuracy for station 7 [33].…”
Section: Resultsmentioning
confidence: 99%
“…TBB's diagnostic effectiveness has been observed to range between 40 and 90 percent in prior research and 68.7% in another investigation. The presence of non-caseating granulomas can be caused by a variety of etiological factors, and accurate clinical correlation can help determine the best treatment strategy (1). TBB was the most used method in the study of Kıter et al, and Sarcoidosis Working Group of Turkish Thoracic Society, which showed a 48.8% success rate (2).…”
Section: Introductionmentioning
confidence: 99%